Teachers' Perceptions of Needs and Supports for Handwriting Instruction in Kindergarten - Jill A. Nye; Divya Sood (Scholarworks @ WMU, 2018)
Background: This study was designed to explore the perceived needs of kindergarten teachers as well as the supports they require in preparing children for success in the area of handwriting. Methods: A phenomenological research design was used and nine kindergarten teachers employed at four elementary schools in a school district in Illinois participated in the study. Semi-structured interviews were completed to discuss the perceptions of teachers related to challenges they face and the supports they require in promoting the occupational task of handwriting among the children in their classrooms. Results: The results from this pilot study revealed that overall the teachers felt that the lack of a curriculum and formalized training impacted their teaching practices related to handwriting instruction. Conclusion: The teachers stated that gaps in their knowledge base relating to developmental progression, the ability to assist struggling students, an awareness of strategies to use, and the IEP process contributed to their challenges in teaching handwriting to kindergarten students.